Effects of Fluoride Use on Oral and Dental Health (Turkey Health Literacy Journal, 2025)
Fluoride has been recognized since the 20th century as one of the most important agents with proven efficacy in preventing dental caries. Dental caries, regardless of the diverse socioeconomic or sociocultural characteristics of countries, emerges as a common public health concern. Research has demonstrated that fluoride prevents the demineralization of teeth against acids derived either from dietary sources or produced by cariogenic bacteria such as Streptococcus mutans. Moreover, fluoride may promote the remineralization of early enamel carious white spot lesions and exert antimicrobial effects by disrupting the mechanisms of cariogenic bacteria. For this reason, in combating dental caries, fluoride has been employed both systemically, such as through water fluoridation, and topically, through methods applied by dental professionals such as fluoride gels. In addition to professional applications, fluoride has also gained widespread use at the community level through individual hygiene and care practices, including fluoridated toothpastes and mouth rinses. The aim of this article is to provide essential knowledge that contributes to health literacy regarding fluoride use, and to present a review on its current applications in dentistry, its mechanisms of caries prevention on dental tissues, and its potential adverse effects.